2009
DOI: 10.1179/136217108x386554
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of solidification cracking in pulsed Nd:YAG laser welding of 2024 aluminium alloy

Abstract: Aluminium alloy AA2024 is one of the most susceptible alloys to solidification cracking. The influence of Nd:YAG laser welding parameters on cracking severity of AA 2024 alloy was studied. Welding was performed in two modes: single spot welding and overlap spot welding. In single spot welding mode, the formation of columnar zone increases cracking severity in the fusion zone. In overlap spot welding mode, the solidification cracks were characterised as: cracks propagated from previous spot, cracks initiated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
(25 reference statements)
2
21
0
1
Order By: Relevance
“…The study found that rectangular laser pulses led to hot cracking in pulsed laser welding of 5456 and 6061 aluminum alloys. This was also presented in the study of Sheikhi et al (2009) who showed that rectangular laser pulses caused hot cracking in 2024 aluminum alloy spot welds and overlapping seam welds. Katayama et al (1997) found that high cooling rates were created by rectangular laser pulses.…”
Section: Introductionmentioning
confidence: 66%
“…The study found that rectangular laser pulses led to hot cracking in pulsed laser welding of 5456 and 6061 aluminum alloys. This was also presented in the study of Sheikhi et al (2009) who showed that rectangular laser pulses caused hot cracking in 2024 aluminum alloy spot welds and overlapping seam welds. Katayama et al (1997) found that high cooling rates were created by rectangular laser pulses.…”
Section: Introductionmentioning
confidence: 66%
“…Due to low heat input and high welding speed, the hybrid laser welding process can generally facilitate the formation of EQZ . It has been demonstrated that fine equiaxed grains in EQZ are surrounded by eutectic structures, indicating a high cracking susceptibility . Besides, both sides of EQZ with the acute microstructural gradient in Figure B are believed to be the weak zone of joints.…”
Section: Resultsmentioning
confidence: 99%
“…6 It has been demonstrated that fine equiaxed grains in EQZ are surrounded by eutectic structures, indicating a high cracking susceptibility. 19 Besides, both sides of EQZ with the acute microstructural gradient in Figure 3B are believed to be the weak zone of joints. The mechanical behavior and improved welding process of this weak zone need to be further explored.…”
Section: Microstructure and Porositymentioning
confidence: 97%
“…열전도도가 높은 알루미늄 합금의 용접에는 고밀도 에너지를 이용한 레이저용접 등이 적용되고 있 으나 [2][3][4][5] , 알루미늄 합금의 용접에서는 고온균열과 같은 결함이 자주 발생한다. 알루미늄합금 용접에서 고온균 열을 방지하기 위하여 결정립 구조를 제어하거나 용착 금속의 화학 조성을 제어하는 방법들이 제안되어 있다 [6][7][8][9][10][11][12][13][14] . [12][13][14]17) .…”
Section: Fig 1 Schematic Diagram Of Laser Scanner Systemunclassified